Acute skin radiation toxicity seen with concurrent T-DM1: A single institutional report of 35 patients. (February 2023) - Dastgheyb, Sana Sara; Kim, Kristine; Doucette, Abigail; Freedman, Gary; Shah, Payal; Makhlin, Igor; Clark, Amy; Taunk, Neil
Abstract: Trastuzumab emtansine (T-DM1) is a novel therapeutic for HER2+ breast cancer patients with residual disease after neoadjuvant chemotherapy. Concurrent radiotherapy (RT) is offered to a subset of patients based on results from the KATHERINE trial which showed a favorable safety profile. With emerging therapies that necessitate concurrent RT, we must closely follow rates of skin toxicity. Our first 35 patients who underwent concurrent T-DM1 treatment with breast/chest wall (CW) ± nodal irradiation are reported. Most patients (22/35) had grade 2+ toxicity and 3 patients had grade 3 toxicities. We add our experience with radiation dermatitis and concurrent T-DM1 to contribute to existing reports.